Accounting for linguistic acculturation, coping, antisociality and depressive affect in the gender role-alcohol use relationship in Mexican American adolescents: a moderated mediation model for boys and girls. Issue 2 (2nd May 2022) - Nagoshi, Julie L.; Kulis, Stephen; Marsiglia, Flavio Francisco; Piña-Watson, Brandy
Abstract: Background: Prior studies have established that gender roles are predictive of substance use for Mexican and Mexican American adolescents, both living in the U.S. and in Mexico. Objectives: The moderating effects of gender and acculturation and the mediating effects of antisociality, depressive affect, and adaptive and avoidant coping on the gender role-alcohol use relationship were examined in a sample of Mexican American adolescents. Methods: Secondary data analyses were conducted on a sample of 955 (450 boys, 505 girls) Mexican American 7th and 8th grade adolescents participating in a school-based substance use intervention. Results: For boys, path analyses yielded significant direct paths from aggressive masculinity to alcohol use. Bootstrapped mediation tests also yielded significant indirect paths through antisociality from assertive masculinity, affective femininity, aggressive masculinity, and the interaction of linguistic acculturation by affective femininity to alcohol use. For girls, the relationship between aggressive masculinity with alcohol use and the negative relationship of affective femininity with alcohol use were also mediated by adaptive coping, which is predictive of decreased substance use. Conclusion/Importance: The present analyses confirm the importance of gender roles, functional mediators, and their interaction with acculturation in predicting substance use in Mexican American adolescents, with implications for the design of interventions to reduce substance use within the Mexican American community.